2006
DOI: 10.1300/j160v06n01_05
|View full text |Cite
|
Sign up to set email alerts
|

The Child in the Family of a Drug-Using Father: Attachment Styles and Family Characteristics

Abstract: The study examined the impact of family characteristics and parental attachment styles on the children of drug-using (DU) fathers in fifty-six families (n = 168) in Israel. Of the DU fathers, 60.7%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…In addition, several studies have examined how attachment styles relate to parents’ perceptions of family functioning. For example, two studies found that parental security was associated with higher ratings of family cohesion and adaptability (Mikulincer & Florian, 1999a; Finzi-Dottan, Cohen, Iwaniec, Sapir, & Wiezman, 2006; yet see Mikulincer & Florian, 1999b, for non-significant results). In addition, Kor et al (2012) found that parents’ avoidance and anxiety were related to greater emotional distance among family members and greater family chaos (i.e., lower organization and control).…”
Section: Review and Analysis Of The Empirical Evidencementioning
confidence: 99%
“…In addition, several studies have examined how attachment styles relate to parents’ perceptions of family functioning. For example, two studies found that parental security was associated with higher ratings of family cohesion and adaptability (Mikulincer & Florian, 1999a; Finzi-Dottan, Cohen, Iwaniec, Sapir, & Wiezman, 2006; yet see Mikulincer & Florian, 1999b, for non-significant results). In addition, Kor et al (2012) found that parents’ avoidance and anxiety were related to greater emotional distance among family members and greater family chaos (i.e., lower organization and control).…”
Section: Review and Analysis Of The Empirical Evidencementioning
confidence: 99%
“…Although consistent research attests the prevalence of insecure attachment representations in adults with substance misuse, a specific association between drug-related disorders and a particular attachment style does not emerge ( 70 , 98 ); indeed, some works have observed a prevalence of the anxious-preoccupied attachment style ( 73 , 78 , 81 , 83 , 99 ), while others have underlined the presence of the dismissing style ( 68 , 71 , 72 , 77 , 82 , 90 , 93 ). Others suggest an association with the unresolved loss and/or trauma (U) pattern ( 73 , 92 , 100 ).…”
Section: Attachment and Parenthood At Risk: Maternal Substance Addictmentioning
confidence: 99%
“…Mothers high in attachment anxiety may wish that they were more involved in their adolescents’ lives and knew more about their activities. In other words, anxious mothers’ perceptions that they lack knowledge about their adolescents’ whereabouts and activities may reflect more general feelings they have about their close relationships – feelings of not being close enough to their relationship partners and fears that partners will want distance – rather than a reflection of actual communication in the parent-adolescent relationship (see Finzi-Dottan, Cohen, Iwaniec, Sapir, & Wiezman, 2006 and Kor, Mikulincer, & Pirutinsky, 2012, for evidence that anxious parents perceive their family relationships as low in cohesion and high in emotional distance). The lack of a connection between mothers’ anxiety and adolescent-reported PK suggests that adolescents may not be systematically withholding information from their parents as a result of their mothers’ concerns about closeness, however.…”
Section: Discussionmentioning
confidence: 99%